Identification of multiple disease resistance in cowpea - Williams, R.J. (1977)
Between 1969 and 1975 the important diseases of cowpea in southern Nigeria were determined, methods to promote epidemics were studied and disease assessment scales were developed. The techniques developed were used to screen 5000 cowpea lines for field resistance-to anthracnose, cercospora leaf spot, rust and bacterial pustule. After preliminary observations on 5000 lines, 719 lines were selected for further evaluation in field disease nurseries. All 719 lines were resistant to at least one of the four diseases, 685 lines were resistant to at least two, 537 lines resistant to at least three, 208 lines were resistant to all four and of these, 28 lines were also resistant to target spot. Preliminary yield evaluation indicated that some of these lines combined multiple resistance with moderate to high yield potential. In a separate study 16 of the multiple resistant lines were found resistant also to two isolates of cowpea (yellow) mosaic virus.